Tuwa’ Pai, Abotoreng, Na Barahala Dalam Penafsiran QS Al-Mā’idah Ayat 90: Studi Komparatif AGH. Daud Ismail dan AGH. Abd. Muin Yusuf - Ahmad Iddal; Achmad Abubakar; Muhsin Mahfudz; Muhammad Ardiansyah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study examines a comparative interpretation of Qur'an Surah Al-Mā'idah verse 90 in the exegeses of AGH. Daud Ismail and AGH. Abd. Muin Yusuf. The study aims to identify the similarities and differences in the interpretive methods and exegetical approaches employed by the two mufassirs in explaining this verse. This research adopts a qualitative library research method using a comparative (muqāran) approach to Qur'anic exegesis. The findings reveal that AGH. Daud Ismail emphasizes a culturally oriented da'wah approach, employing language that is closely connected to the Bugis community, whereas AGH. Abd. Muin Yusuf presents a more systematic and rational explanation of the verse's content. Despite differences in their interpretive methods and styles, both mufassirs consistently affirm the prohibition of intoxicants (khamr), gambling, idol worship, and divination by arrows (al-azlām). This study demonstrates that local Qur'anic exegesis plays a significant role in bringing the message of the Qur'an closer to society by adapting it to local cultural and social contexts.